Palladium bis(phosphinite) 'PCP'-pincer complexes and their application as catalysts in the Suzuki Reaction - DRAPER, SYLVIA MARY (My University, 2000)
Palladium complexes of inexpensive, easily synthesised bis(phosphinite) `PCP ?-pincer ligands show good activity in the Suzuki coupling of deactivated and sterically hindered aryl bromides
PUBLISHED
Keywords: Chemistry